Determining Factors for House Purchasing Decisions in Batam City - Jacky, Jacky; Saputra, Suyono (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The research was conducted to test the relationship between independent and dependent variables using mediating variables. The object of research is the people of Batam City who are interested in buying a house. The data obtained is primary data by distributing a research questionnaire containing 31 questions. The number of respondents collected was 310 respondents. The research results found that there was a significant influence between the variables product quality, price, location, and promotion, E-WOM had a positive influence on purchasing decisions mediated by the purchase interest variable. This empirical study has limitations in collecting data sources due to the high house prices in Batam city, as well as limited sources supporting several research variables. These limitations form several suggestions for future researchers to expand research locations and link house purchase decisions with investment goals, due to the increasing topic of investment literacy which is a current trend.